2006
DOI: 10.1021/jf061200i
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Starch Synthase I Effects Differences in Amylopectin Structure betweenindicaandjaponicaRice Varieties

Abstract: The effect of soluble starch synthase I (SSI) on differences of amylopectin structure between the indica and japonica rice varieties was investigated. Native-PAGE/active staining analysis showed that the SSI activity of an indica rice variety, "Kasalath", was significantly lower than that of a japonica rice variety, "Nipponbare", and that the low activity in "Kasalath" was maintained during seed development. The result of northern blot analyses suggests that the low expression of SSI in "Kasalath" is controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…Nakamura et al have reported starch synthase IIa as a key-enzyme to discriminate Japonica and Indica rice. 29) We have reported that the starch debranching enzyme 9) and starch synthase I 30) were also discriminative enzymes between Indica and Japonica rice.…”
Section: Discrimination Of Japonica and Indica Rice Based On The Retrmentioning
confidence: 98%
See 1 more Smart Citation
“…Nakamura et al have reported starch synthase IIa as a key-enzyme to discriminate Japonica and Indica rice. 29) We have reported that the starch debranching enzyme 9) and starch synthase I 30) were also discriminative enzymes between Indica and Japonica rice.…”
Section: Discrimination Of Japonica and Indica Rice Based On The Retrmentioning
confidence: 98%
“…A rice flour sample (1.0 g) was suspended for 15 min in 5 mL of a 0.04 M acetate/ phosphate buffer at pH 4.6 and room temperature (lower than 30 C) before being centrifuged for 10 min at 1;000 Â g. A 0.5 mL aliquot of an Azo-Barley glucan substrate solution and 0.5 mL aliquot of the enzyme extract were mixed and pre-warmed to 30 C for 5 min. The mixture was vigorously agitated and then incubated at 30 C for exactly 10 min, before being combined with 3.0 mL of precipitant solution A and vigorously stirred. The tube was allowed to stand at room temperature for 5 min, stirred again, and then centrifuged for 10 min at 1;000 Â g. The absorbance of the supernatant of each sample solution was measured at 590 nm against the reaction blank of distilled water.…”
Section: )mentioning
confidence: 99%
“…3). Takemoto-Kuno et al (2006) reported that the allelic difference in SSI between japonica Koshihikari and indica Kasalath affected the amylopectin chain-length distribution in F 2 and F 3 progenies. When SSI expression was decreased to between 0 and 20% by retrotransposon Tos17 insertion, the amount of dp 8-12 decreased and that of dp 6-7 and 16-19 increased (Fujita et al, 2006).…”
Section: Characterization Of Nils In Relation To Starchmentioning
confidence: 99%
“…Detailed analysis can be performed only by dissecting the wx and SSIIa loci, both of which are located on the short arm of chromosome 6. Moreover, the starch synthase I (SSI) locus, positioned between wx and alk, also could affect the amylopectin chain-length distribution and the gelatinization properties of starch (Takemoto-Kuno et al, 2006).…”
mentioning
confidence: 99%
“…SSIV is closely related to SSIII; both have similar structures (Leterrier et al, 2008). Further reverse genetic studies showed that impaired SSI expression was reported to result in structurally altered amylopectin in Arabidopsis leaves (Delvallé et al, 2005) and rice endosperm (Takemoto-Kuno et al, 2006; Fujita et al, 2008). Inhibition of SSII gene expression gave rise to lower pasting temperature as the result of alterations in amylopectin structure (Edwards et al, 1999).…”
Section: Introductionmentioning
confidence: 99%